The ethnographer as accomplice—Edifying qualms of bureaucratic fieldwork in Kafka's penal colony. (June 2019) - Martin, Tomas Max
This article explores the ethnographer's equivocal role as an accomplice of bureaucratic power through a reading of Kafka's short story "In the Penal Colony." The researcher's position when enrolled and affined in the bureaucratic field, which Kafka so uncannily animates, is illustrated via four ethically charged fieldwork experiences in Ugandan, Indian, and Myanmar prisons. I argue that these experiences were telling situations of "edifying qualms, " which were both morally ambiguous and analytically generative. The article concludes by suggesting that methodological attention to these edifying qualms enables ethnographers to use their deep-set complicity with bureaucratic violence as an antenna for picking up the impure pragmatics of doing "less harm, " and for imagining a better world altogether.